Groundwater dynamics in intertidal zones of beach aquifers during salt-fingering flow - Fang, Yunhai; Qian, Jiazhong; Ma, Lei; Wang, Huan (Frontiers in Marine Science, 2023)
At aquifer-sea interfaces, submarine groundwater discharge (SGD) and related chemical loads are closely related to groundwater environment in the intertidal zone of coastal aquifers. Although unstable salinity distribution in the intertidal zone associated with salt-fingering flow has been known as a natural phenomenon for some coastal aquifers, a quantitative understanding of groundwater dynamics in the intertidal zone during salt-fingering flow is still lacking. This study investigated the movement features of salt fingers and the response laws of freshwater discharge zone (FDZ) in the intertidal zone, considering the fixed and seasonal inland conditions. The results revealed that during salt-fingering flow, the finger was repeatedly generated and detached from the intertidal zone. Horizontally, the finger moved toward the sea, and the finger speed first increased at the development stage, then remained unchanged at the separation stage, and finally decreased at the mergence stage. The movement speed of salt fingers was closely related to ambient freshwater flow in the FDZ. In the vertical direction, the finger first permeated downward with a decreasing speed, and then the upward discharge of fresh groundwater in the FDZ region with an increased flow velocity pushed the finger upwards with an increasing speed. In contrast to the results in a stable intertidal regime, the width of FDZ at the aquifer-sea interface fluctuated over time, and the variation trends possessed a well agreement with the flux of fresh groundwater discharge. This suggested that the width of FDZ at the aquifer-sea interface can be used as an indicator of fresh groundwater discharge, even in an unstable regime, to provide a basis for field monitoring. The intensity of salt-fingering flow varied over time under the condition of seasonal freshwater inflow. The mean duration of salt fingers decreased slightly with the increase of seasonal freshwater periods due to a decrease in the interface perturbation for the intertidal environment. These findings lay the foundation for gaining a better understanding of the potential implications of salt-fingering flow on SGD and related solute transports.